Structural and Functional Model of Forming the Readiness of Future Special Forces Specialists for Professional Activity - Rudynskyi, Vitalii (Pedagogical Discourse, 2024)
The article highlights the importance of training military specialists in the modern conditions of the functioning of the Armed Forces of Ukraine. The legislation of Ukraine on the transformation of military education and NATO training standards proves that the training of cadets in higher military educational institutions requires modernization and innovative approaches to conducting the educational process. An analysis of the educational training of future officers abroad, whose training experience is being introduced into the professionalization of military education in Ukraine to form the compatibility of the Armed Forces of Ukraine and the armed forces of NATO member states, was conducted. The basic requirements for the professional training of cadets were identified and the dependence of the new level of training on innovative educational innovations and the proper functioning of higher military educational institutions in a mixed form of education was noted. To predict the innovative educational process of training a bachelor of military management in the speciality 253 Military Management (by type of armed forces) and study it more holistically, pedagogical modelling was used as a method of researching objects of scientific knowledge. Within the framework of the process of systematic research of the formation of readiness of future special-purpose specialists for professional activity in conditions of mixed education, a structural-functional model was chosen. It is determined that the basis for building the model is scientific innovative paradigmatic approaches (systemic, competency-based, personality-oriented, creative, anthropological, cultural, sociological, informational and technological) and general pedagogical and specific principles that serve as defining guidelines in achieving the quality of professional training. The content of each of the structural blocks (targeted, theoretical, content, functional-methodical and result-based-evaluation) is characterized, which reveals the fundamental aspects of the formation of the readiness of special-purpose specialists for future activities.